The intersection of semiotics and phenomenology Peirce and Heidegger in dialogue - Kemple, Brian A. (Semiotics, communication and cognition, 2019)
Many contemporary explanations of conscious human experience, relying either upon neuroscience or appealing to a spiritual soul, fail to provide a complete and coherent theory. These explanations, the author argues, fall short because the underlying explanatory constituent for all experience are not entities, such as the brain or a spiritual soul, but rather relation and the unique way in which human beings form relations. This alternative frontier is developed through examining the phenomenological method of Martin Heidegger and the semiotic theory of Charles S. Peirce. While both of these thinkers independently provide great insight into the difficulty of accounting for human experience, this volume brings these insights into a new complementary synthesis. This synthesis opens new doors for understanding all aspects of conscious human experience, not just those that can be quantified, and without appealing to a mysterious spiritual principle.